Peran Studi Islam dalam Membangun Pemahaman Hukum Berbasis Nilai-nilai Qur'ani - Tamama Zuhriyah; Fera Ailinia Istifa; Wahyu Wibowo; Syarifah Salimah Nailulmuna (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
This article discusses the important role of Islamic studies in building an understanding of law based on Qur'anic values. In the midst of the complexity of modern legal challenges, approaches that integrate Islamic teachings with contemporary legal principles are becoming increasingly relevant. Through analysis of Qur'anic texts and interpretations of scholars, this article identifies the moral and ethical values ​​contained in Islamic teachings and how these values ​​can be applied in the legal system. This research also explores the contribution of Islamic studies in creating a legal framework that is not only fair and just, but also reflects social justice and community welfare. Using qualitative methods, this article presents various perspectives from Islamic legal experts and academics, as well as case studies that show the application of Qur'anic values ​​in legal practice. It is hoped that the findings from this article can make a significant contribution to the development of law that is more inclusive and responsive to the needs of society, as well as strengthening the position of Islamic studies as a relevant scientific discipline in the current legal context.